2019
DOI: 10.1111/efp.12560
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Eucalyptus grandis and Acacia mearnsii seedlings to five Phytophthora species common in South African plantations

Abstract: Eucalyptus grandis and its hybrids, as well as Acacia mearnsii, are important non‐native trees commonly propagated for forestry purposes in South Africa. In this study, we conducted pathogenicity trials to assess the relative importance of five commonly isolated Phytophthora spp. (Phytophthora alticola, P. cinnamomi, P. frigida, P. multivora and P. nicotianae) from the plantation environment on E. grandis and A. mearnsii seedlings. Overall E. grandis was more susceptible to the tested Phytophthora spp. than A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…These results agree with those found by Bose et al (2019) who concluded that P. alticola was few aggressive when was inoculated in E. grandis . Regarding the low recoveries of these species in our pathogenicity trials (33%–66%), these results are consistent with those of Bose et al (2019) where P. alticola recovery rate was 30%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with those found by Bose et al (2019) who concluded that P. alticola was few aggressive when was inoculated in E. grandis . Regarding the low recoveries of these species in our pathogenicity trials (33%–66%), these results are consistent with those of Bose et al (2019) where P. alticola recovery rate was 30%.…”
Section: Discussionsupporting
confidence: 93%
“…Despite of this, no one of the inoculated seedlings died nor wilted, probably because they were frequently watered and did not suffer drought stress at any time. These results agree with those found by Bose et al (2019) who concluded that P. alticola was few aggressive when was inoculated in E. grandis . Regarding the low recoveries of these species in our pathogenicity trials (33%–66%), these results are consistent with those of Bose et al (2019) where P. alticola recovery rate was 30%.…”
Section: Discussionsupporting
confidence: 93%